2006
DOI: 10.1242/jcs.02779
|View full text |Cite
|
Sign up to set email alerts
|

APC inhibits ERK pathway activation and cellular proliferation induced by RAS

Abstract: Inactivating mutations in the adenomatous polyposis coli gene (APC), and activating mutations in RAS, occur in a majority of colorectal carcinomas. However, the relationship between these changes and tumorigenesis is poorly understood. RAS-induced activation of the ERK pathway was reduced by overexpressing APC in DLD-1 colorectal cancer cells. ERK activity was increased by Cre-virus-induced Apc knockout in primary Apcflox/flox mouse embryonic fibroblasts, indicating that APC inhibits ERK activity. ERK activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
3

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 53 publications
3
75
1
3
Order By: Relevance
“…These observations provide a molecular explanation for our failure to see phenotypic changes after activation of K-ras V12 expression. These data also argue against the notion that Apc inhibits activation of the Raf-MEK-ERK pathway in vivo, as recently suggested (16). Interestingly, nuclear P-MEK and P-ERK were observed in goblet cell nuclei, suggesting that this pathway may be relevant to goblet cell differentiation (Fig.…”
Section: Raf-mek-erk and Wnt Signaling Pathways Are Not Dysregulated supporting
confidence: 51%
“…These observations provide a molecular explanation for our failure to see phenotypic changes after activation of K-ras V12 expression. These data also argue against the notion that Apc inhibits activation of the Raf-MEK-ERK pathway in vivo, as recently suggested (16). Interestingly, nuclear P-MEK and P-ERK were observed in goblet cell nuclei, suggesting that this pathway may be relevant to goblet cell differentiation (Fig.…”
Section: Raf-mek-erk and Wnt Signaling Pathways Are Not Dysregulated supporting
confidence: 51%
“…Our previous observations that Axin and Apc destabilize Ras (Park et al, 2006;Jeon et al, 2007) led us to investigate a mechanism for Ras degradation. The half-lives of both Ras and β-catenin werẽ 9 hours in HEK293 cells in which new protein synthesis was inhibited (Fig.…”
Section: Both Endogenous and Overexpressed H-ras Proteins Are Regulatmentioning
confidence: 99%
“…We also found that Axin and adenomatous polyposis coli (Apc), the negative regulators of Wnt/β-catenin signaling, increased degradation and polyubiquitylation of H-Ras by enhancing the β-TrCP-H-Ras interaction. The regulation of H-Ras stability by Wnt/β-catenin signaling controls cellular proliferation and transformation (Park et al, 2006;Jeon et al, 2007). β-TrCP and Axin synergistically affected cellular transformation, suggesting that these proteins are crucial signaling intermediates facilitating Wnt/β-catenin control of H-Ras stability and cellular transformation.…”
mentioning
confidence: 99%
“…The ERK pathway is one of the major transforming signaling pathways, and the cross-talk between the ERK and the Wnt/β-catenin pathways was identified in several of our previous experiments (Yun et al, 2005;Park et al, 2006;Jeon et al, 2007). The ERK pathway is immediately activated by recombinant Wnt3a (Yun et al, 2005), and is also regulated by adenomatos polyposis coli (APC), the negative regulator of the Wnt/β-catenin pathway (Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ERK pathway is immediately activated by recombinant Wnt3a (Yun et al, 2005), and is also regulated by adenomatos polyposis coli (APC), the negative regulator of the Wnt/β-catenin pathway (Park et al, 2006). Although both the Wnt/β-catenin pathway and the PI3K/Akt pathway are involved in tumor progression, the relationship between these two pathways is poorly understood.…”
Section: Introductionmentioning
confidence: 99%